Retraction Note to: High systemic levels of the cytokine-inducing HMGB1 isoform secreted in severe macrophage activation syndrome - Karin Palmblad; Hanna Schierbeck; Erik Sundberg; Anna-Carin Horne; Helena Erlandsson Harris; Jan-Inge Henter; Daniel J. Antoine; Ulf Andersson (BMC, 2020)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s10020-020-00263-2